Hybrid approach for multi-node localization and Identification - Hasan, Ola A.; Rashid, Abdulmuttalib T.; Ali, Ramzy S. (Basrah Journal for Engineering Sciences, 2016)
In this paper, a new approach for the positioning (localization) of multi-node systems is presented. Each node including the beacon node contains two types of sensors: one for the distance sensing and the other type is for communication. The main idea of our proposed approach is to use the control of beacon to construct a nodes' tree which is going to be used later by the nodes to know the paths in which the information will flow. During the tree construction the identities of nodes will be known. Every node except the beacon will use the information obtained from its previous neighbor in the tree to find its own location and orientation. Several simulations using visual basic 2012 are implemented to discern the performance of this algorithm.